2021
DOI: 10.3390/ijms22169060
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exosome and the ESCRT Pathway on Enveloped Virus Infection

Abstract: The endosomal sorting complex required for transport (ESCRT) system consists of peripheral membrane protein complexes ESCRT-0, -I, -II, -III VPS4-VTA1, and ALIX homodimer. This system plays an important role in the degradation of non-essential or dangerous plasma membrane proteins, the biogenesis of lysosomes and yeast vacuoles, the budding of most enveloped viruses, and promoting membrane shedding of cytokinesis. Recent results show that exosomes and the ESCRT pathway play important roles in virus infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 131 publications
(173 reference statements)
0
27
0
Order By: Relevance
“…These proteins function in manipulating membrane bilayers in a variety of essential cellular physiological and metabolic processes, such as multivesicular body (MVB) formation, membrane abscission in cytokinesis, exosome and microvesicle biogenesis, nuclear envelope reconstruction, plasma membrane repair, neuron pruning, autophagosome closure, and lysosome repair ( 23 28 ). In addition, the ESCRT machinery is reported to be utilized by viruses from diverse families to support their infections at various stages ( 29 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…These proteins function in manipulating membrane bilayers in a variety of essential cellular physiological and metabolic processes, such as multivesicular body (MVB) formation, membrane abscission in cytokinesis, exosome and microvesicle biogenesis, nuclear envelope reconstruction, plasma membrane repair, neuron pruning, autophagosome closure, and lysosome repair ( 23 28 ). In addition, the ESCRT machinery is reported to be utilized by viruses from diverse families to support their infections at various stages ( 29 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…ESCRT is a family of proteins that includes ESCRT-0, -I, -II and -III ( 31 ). These proteins bind to MVB membrane-associated proteins and regulate the targeted transport of cellular cargo molecules and the formation of ILVs ( 32 ). Also involved in the formation of MVBs are tumor susceptibility gene 101 and other ESCRT cofactors, such as ALG-2 interacting protein X ( 33 ) and vacuolar protein sorting-associated protein 4 ( 34 ).…”
Section: Characteristics Classification and Biosynthesis Of Extracell...mentioning
confidence: 99%
“…A broad range of research has indicated an ESCRT-independent route in the exosome synthesis and carrier packing of lipids and related proteins, including tetraspanine ( 28 ). In opposition to ESCRT-sorted proteins, the loading of RNA into exosomes becomes lipid-mediated, reliant on self-organizing fat and carrier motifs.…”
Section: Exosome’s Biologymentioning
confidence: 99%
“…Glioma cell exosomes transport different chemicals than regular glial cell exosomes ( 40 ). Cancer effectors such as a mutant oncoprotein, oncogenic transcripts, and miRNAs are among the elements involved in tumor formation ( 28 ). In addition, exosomes enhance communication between cancer cells and the stromal cells surrounding them, resulting in either the tumorigenesis of apparently normal cells or a change in their behavior, which offers a favorable environment for the tumor to grow ( 41 ).…”
Section: The Roles Of Exosomes In Glioma Developmentmentioning
confidence: 99%